(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: The major therapeutic failure in clinical settings is due to problematic biofilm-producing bacteria like Pseudomonas aeruginosa. This study aims to investigate the effect of dual-species biofilms, monosaccharide, and D-amino acids on pseudomonal biofilm. Methodology: A total of 130 patients with catheter-associated urinary tract and wound infections were involved in this study. Quantitative biofilm assay by alginate beads was performed. The dual-species biofilms have been done, and the effect of ciprofloxacin, monosaccharides, and D-amino acids on sessile cells was detected. Conclusion: This study suggested that the combined action of both monosaccharides (glucose and galactose) and the combination of each one with ciprofloxacin is the enhancing of P. aeruginosa biofilm and increases survival strategy against ciprofloxacin. In contrast, a noticeable biofilm reduction and marked synergistic action for ciprofloxacin have been determined in the combination of the two D-amino acid, alanine, and glycine in comparison to the effect of each one alone. Furthermore, the dual biofilm of P. aeruginosa with each of K. pneumonia and E. coli, markedly reduced pseudomonal biofilm, while co-culture with S. aureus revealed strong support of pseudomonal pathogenicity and increased its biofilm production.